Reduction in STIs in an empowerment intervention programme for female sex workers in Bangalore, India: the Pragati programme - Dennis Souverein; Sjoerd M. Euser; Rajendra Ramaiah; Pushpalatha Rama Narayana Gowda; Chandra Shekhar Gowda; Diana C. Grootendorst; Snehal Barot; Françoise Jenniskens; Sunil Kumar; Shiv Kumar; Jeroen W. Den Boer (Taylor & Francis Group, 2013)
Background/Objective: The Pragati programme is an on-going empowerment programme for female sex workers (FSWs) working and living in Bangalore, India. Pragati aims to reduce transmission of HIV and sexually transmitted infections (STIs) among FSWs. This study describes the STI incidence rate, contact rate, and condom use during follow-up years. Design: Between April 2005 and November 2010, 20,330 FSWs participated in the programme. Outcome measures were programme exposure (number of contacts per person-year), STI incidence rate, and condom use. All analyses were stratified by year of follow-up. STIs were diagnosed by syndromic case management in either programme or referral clinics. We restricted our analyses to the period between April 2005 and July 2008 (when the majority of STIs were diagnosed in programme clinics), in order to minimise the possible influence of differences in STI diagnosis between clinic types. Results: Results showed a significant increase of programme exposure (p-value for trend < 0.001) and a significant decrease in the STI incidence rate (p-value for trend < 0.001) over the follow-up time (between April 2005 and July 2008). Reported condom use at last paid sex increased from 77.6% in year 1 to 100% in year 4 of follow-up (p-value for trend < 0.001). Conclusion: Our data seem to suggest that the Pragati programme had a positive effect on the STI incidence rate and condom use, possibly as a result of increased programme exposure. We recommend for future studies to invest more in the study design, type of data collection, and recording mechanisms before starting with an intervention. Incorporation of empowerment strategies as an approach in HIV prevention programmes can have a beneficial effect on the lives and livelihoods of FSWs.